Shorter fixation durations for up-directed saccades during saccadic exploration: A meta-analysis - Harold H. Greene; James M. Brown; Gregory P. Strauss (Journal of Eye Movement Research)
Utilizing 23 datasets, we report a meta-analysis of an asymmetry in presaccadic fixation durations for saccades directed above and below eye fixation during saccadic exploration. For inclusion in the meta-analysis, saccadic exploration of complex visual displays had to have been made without gaze-contingent manipulations. Effect sizes for the asymmetry were quantified as Hedge’s g. Pooled effect sizes indicated significant asymmetries such that during saccadic exploration in a variety of tasks, presaccadic fixation durations for saccades directed into the upper visual field were reliably shorter than presaccadic fixation durations for saccades into the lower visual field. It is contended that the asymmetry is robust and important for efforts aimed at modelling when a saccade is initiated as a function of ensuing saccade direction.